Current Ideas on the Treatment Of Diabetic Neuropathies. Issue 2 (3rd March 2016) - Anderson, Dustin; Zochodne, Douglas W.
ABSTRACT: Diabetic neuropathies are common and their prevalence is rising with the growth in the global prevalence of type 2 diabetes. Several patterns of neuropathy have now been described, with diabetic sensorimotor polyneuropathy (DPN) being the most common. Autonomic neuropathy, entrapment neuropathies including carpal tunnel syndrome and ulnar neuropathy at the elbow pose additional burdens. DPN can be detected in over half of all diabetic subjects and approximately 20% of all patients with DPN also experience neuropathic pain, a complication with major impacts on quality of life. Currently, the only available treatments for DPN are optimal glucose control and pain management, whereas interventions, beyond optimizing hyperglycemic control, to address the underlying polyneuropathy are not available. Here we review current treatment options and new literature relating to DPN, with an emphasis on novel and emerging treatments.